How Small Businesses are changing their Traditional Marketing Strategy with Digital marketing provided by TEN’s 360? - Ove, Riaz Uddin (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.